A Detection Performance Analysis of Sanya Incoherent Scatter Radar Tristatic System. Issue 5 (29th April 2021) - Zhang, Ning; Li, Mingyuan; Zhao, Biqiang; Zeng, Lingqi; Yue, Xinan; Hao, Honglian; Wang, Junyi; Ding, Feng; Ning, Baiqi; Wan, Weixing
Abstract: Incoherent scatter radars (ISR) are among the most powerful ground‐based instruments for solar‐terrestrial physics, measuring multiple plasma parameters over almost the entire vertical extent of the ionosphere. In Sanya, on Hainan Island, China, an advanced high‐power phased array ISR, known as the Sanya incoherent scatter radar (SYISR), is under construction. A tristatic system is planned, with a transmitter at Sanya (SY) Station (109.6°E, 18.3°N), together with receivers at SY, Fuke (FK) (109.1°E, 19.5°N), and Qiongshan (QS) (110.2°E, 19.7°N) on Hainan Island. With the pulse width increasing, the SNR increases for a phased array monostatic ISR, while the SNR initially increases and then remains unchanged for a phased array bistatic ISR. SNR first increases and then decreases as the detection height increases from 100 km to 1, 000 km for both the monostatic and bistatic ISR for typical ionospheric conditions. The relative error decreases fast with increasing pulse width when the pulse width is lower than 130 μs for both monostatic and bistatic ISR. When the pulse width is over 130 μs, the relative error decreases very slowly for a monostatic ISR, while it decreases very slowly and then stays unchanged with increasing pulse width for a bistatic ISR. Relative error increases slowly below 500 km, but increases fast for heights over 500 km for both the monostatic ISR and bistatic ISR. It is shown that a tilt angle of 20°–30° and a clockwise‐rotation angle of 157° are reasonable choices for the FK receiving array in the SYISR tristatic system. Key Points: Multistatic phased array Incoherent scatter radars (ISR) equation for soft target is derived The detection performances of phased array monostatic and bistatic ISR are analyzed for pulse width, height, beam width and scattering volume Optimal tilt and rotation angles of receiving array are suggested for Sanya incoherent scatter radar (SYISR) tristatic system